Intestinal virome and normal microflora of human: features of interaction - Bobyr, V; Ponyatovsky, V; Djugikowa, E; Shyrobokov, V (Annals of Mechnikov's Institute, 2020)
Summary: Intestinal bacteria defend the host organism and narrow pathogenic bacterial colonization. However, the microbiome effect to enteric viruses is unexplored largely as well as role of microbiota in the pathogenesis of viral infections in general. This review focuses on precisely these issues. Keywords: microbiome, virome, normal microflora, enteric viruses, contagiousness. In this review article, facts about viral persistence in the human gut are summarized. It is described the role of viral populations during health and diseases. After analyzing of the literary facts it was concluded that the gastrointestinal tract is an environment for one from the most complex microbial ecosystems, which requires of more deeper study of its composition, role in physiological processes, as well as the dynamics of changes under influence of the environment. Normal microflora performs a different important functions providing the physiological homeostasis of the human body, including, in particular, an important role in the human metabolic processes, supporting of homeostasis, limiting of colonization by infectious bacteria. The multifactorial significance of the normal gastrointestinal microflora can be divided into immunological, structural and metabolic functions. At the same time, interaction between intestinal microflora and enteric viruses has not been studied largely. In recent years, much attention is paid to study of viruses-bacteria associations, and it is possible, obtained results should change our understanding of microbiota role in the systematic pathogenesis of the diseases with viral etiology. In contrast to the well-known benefits of normal microflora to the host, the viruses can use intestinal microflora as a trigger for replication at the optimal region. Recent studies give a reason for assumption that depletion of normal microflora with antibiotics can determining the antiviral effect. Thus, the role of commensal bacteria in viral transmission and pathogenesis is clarified. Probably, bacterial microflora can implement the protective role as well as be abettor of virus. However, an understanding of interaction between microbiota and virus during viral disease may initiate the introduction of new antiviral strategies. Further research is needed to determining the features of relationship between viruses and bacteria in the development of infectious process, and analyze whether the viral and bacterial agents form a symbiotic relationship in human body. This review focuses on precisely these issues.